Evaluating the macro and micro geographic mechanisms that modulate the coexistence between sympatric Sturnira bat species - Saldaña-Vázquez, Romeo A. (2023)
One of the key questions in ecology is to understand the mechanisms that modulate the coexistence between sympatric species. Climate and habitat perturbation gradients have been proposed as moderators of species coexistence. The first is related to availability and the diversity of food resources. The second is related to change in habitat structure that promotes changes in plant structure and diversity that impacts the diversity of other organisms. Although there is empirical evidence that supports these mechanisms to explain coexistence, they have not been evaluated quantitatively and on a wide geographic scale. Using phytophagous bat species of the genus Sturnira we evaluated both mechanisms. These bats are morphologically similar and are key organisms for the seed dispersal of Neotropical forest plants. Using systematic review protocols, we obtained data of the occurrence and relative abundance of sympatric Sturnira species of different Neotropical forests. We used generalized linear models to evaluate the predictor power of Holdridge’s life zones and habitat disturbance type to explain the evenness of sympatric Sturnira species. Life zones did not explain the variation in evenness of sympatric species of Sturnira. However, we found that the type of disturbance and individuals captured explain the variation of evenness in Sturnira species. Grasslands present the higher Sturnira species evenness, while sites with lower bat captures had higher evenness. These suggest that the reduction of vegetation complexity allows the coexistence among these highly related species, via the reduction of their relative abundances.